Prevalence of Sports‐Related Injuries and Illnesses in Paralympic Athletes. Issue 3 (23rd October 2019) - Fagher, Kristina; Dahlström, Örjan; Jacobsson, Jenny; Timpka, Toomas; Lexell, Jan
Abstract : Background: With increased participation in Paralympic sports, the burden of sports‐related injuries and illnesses may increase. However, there is limited knowledge about the epidemiology of sports‐related injuries and illnesses in Paralympic sports (SRIIPS). Objective: To describe among Swedish Paralympic athletes the 1‐year retrospective period prevalence of severe SRIIPS and the point prevalence of all SRIIPS and to examine differences in prevalence proportions between athletes with different impairments, behaviors, and sport characteristics. Design: Cross‐sectional study. Setting: Swedish Paralympic Programme. Participants: One hundred and four Paralympic athletes with visual, physical, and intellectual impairment. Methods: An eHealth application adapted to Paralympic athletes was used to collect self‐report data on existing and previous SRIIPS, as well as impairment, behavior, and sport characteristics. Main Outcome Measurements: One‐year retrospective period prevalence and point prevalence. Results: The period prevalence of severe injuries was 31% (95% CI 23‐40) and the point prevalence 32% (95% CI 24‐41). The period prevalence of severe illnesses was 14% (95% CI 9‐23), and 13% of the athletes (95% CI 8‐22) reported a current illness. More severe injuries (P <.05) were reported by athletes aged 18 to 25 years, not using assistive device, having pain during sport, using analgesics, continuing training injured, and feeling guilt when missing exercise. Athletes who reported a previous severe injury, having pain in daily life and during sport, using analgesics, and being upset when unable to exercise had a higher prevalence of current injuries (P <.05 ) . Being female, reporting previous severe illness, using prescribed medication, and feeling anxious/depressed were features associated with ongoing illnesses (P <.05 ) . Conclusion: Paralympic athletes report a high prevalence of SRIIPS. Behavioral and psychological aspects as well as pain and use of medication appear to be associated with the occurrence of SRIIPS. The results imply that factors leading to SRIIPS are complex and call for a broad biopsychosocial approach when developing preventive measures. Level of Evidence: III.